Analisis Pengelolaan Risiko Kebakaran Hutan Berbasis Komunitas di Kabupaten Kampar - Oktorina, Fenty Kurnia; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman (Innovative: Journal Of Social Science Research, 2024)
Forest and land fires pose a significant environmental threat in Kampar Regency, Riau Province, which is characterized by extensive and fire-prone peatlands. Community-based approaches have been identified as a vital strategy to enhance public participation in fire prevention and mitigation. This study evaluates the effectiveness of community-based fire risk management, focusing on the role of communities, challenges faced, and the policy support required. The study employs the Semantic Literature Review (SLR) method to integrate and analyze relevant literature. Data were collected from academic journals, policy reports, and other secondary sources, filtered using keywords such as "forest fires" and "community-based approaches." Key themes were explored to identify patterns and interconnections influencing fire risk management. The analysis reveals that community-based approaches are effective in raising public awareness but face challenges such as limited resources, insufficient training, and a lack of coordination with external stakeholders. Recommendations include strengthening policy support, enhancing community capacity, and developing early warning systems. In conclusion, this approach holds significant potential to reduce fire risks if supported by sustainable policies and multi-stakeholder collaboration.